Development of spectrum management tool for malaysia using open-source GIS software - Saman M.A.; Ismail A.F.; Badron K.; Ramli H.A.M.; Hashim W.; Atiqullah Fakrullah A.N. (Springer Verlag, 2023)
Cellular telephone systems; Cost effectiveness; Global system for mobile communications; Mobile telecommunication systems; Open source software; Open systems; Changing environment; Commercial software; Global system for mobile communications (GSM); Mobile communication technology; Mobile Technology; Spectrum management; Spectrum planning; Universal mobile telecommunications systems; 3G mobile communication systems